PENGINTEGRASIAN KREATIVITI SAINTIFIK DALAM PENGAJARAN SAINS (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This decade, the flow of world education system has changed as a result of competition globally. To put Malaysia in line with international education system, integrating creativity in the teaching of science is very important. However , previous studies have shown that critical elements are still not able to fully practice caused by a variety of obstacles and constraints of the education system itself. This concept paper will explore the importance of integrating creativity towards improving student achievement in science. Implementation of the learning process will also be seen in terms of the willingness of teachers , pedagogical skills and attitudes of teachers and students. This discussion also will explore the factors that motivate creativity , issues and challenges of scientific creativity in the classroomKey words: integrating creativity, science subject